PEMBERDAYAAN UMKM MELALUI KOPERASI PADA KECAMATAN LEUWIDAMAR, KABUPATEN LEBAK, BANTEN - Suharyati Suharyati; Ediwarman Ediwarman; Nobelson Nobelson (Jurnal Bakti Masyarakat Indonesia, 2021)
The era of globalization and digitalization have the impact of narrowing the space for cooperatives and fierce competition. Cooperatives contribute to the Indonesian economy, and to improve people's welfare. The activity of empowering MSMEs through cooperatives is expected to be able to contribute to optimizing MSMEs. The participants of the activity were 30 craftsmen in Kanekes village, Leuwidamar sub-district. Activities carried out by lectures and discussions method about the roles and benefits of cooperatives for MSMEs. Participants were also given a questionnaire to fill in demographic data and a test of understanding of cooperatives. Based on the results, it was found that the largest number of participants were at the productive age, had a typical Baduy business. The business is a home business with an average number of employees of two people who are family members. The amount of capital is in the range of IDR 10,000,000 to 25,000,000 in the form of own capital. The monthly income received is ≤ 1.000.000,- because the business is on a micro-scale. Business age ≤ 2 years, the training participants are relatively new business actors. As for financial services through cooperatives, 77% of participants did not use them. The test results show an understanding of cooperatives by 86% and an interest in becoming a cooperative member by 80%, which means that after being given provisioning, the participants really understand the role of cooperatives for MSMEs and are interested in becoming cooperative members ABSTRAK:Era globalisasi dan digitalisasi cenderung memiliki dampak mempersempit ruang gerak koperasi, dan persaingan ketat. Koperasi berkontribusi bagi perekonomian Indonesia, dan merupakan wadah untuk meningkatkan kesejahteraan masyarakat. Kegiatan pemberdayaan UMKM melalui koperasi ini diharapkan mampu memberikan kontribusi dalam mengoptimalkan UMKM untuk berpartisipasi pada koperasi. Peserta kegiatan adalah pengrajin di desa Kanekes, kecamatan Leuwidamar sebanyak 30 orang. Kegiatan dilaksanakan dengan metode ceramah dan diskusi mengenai peran dan manfaat koperasi bagi UMKM. Pada akhir kegiatan peserta diberikan kuesioner untuk mengisi data demografi dan test pemahaman mengenai perkoperasian. Berdasarkan hasil deskripsi data peserta diperoleh jumlah terbesar usia peserta berada pada usia produktif, memiliki usaha kerajinan khas suku baduy, seperti kain tenun, tas koja, souvenir. Usaha yang dilakukan berupa usaha rumahan dengan jumlah karyawan rata-rata dua orang yang merupakan anggota keluarga. Jumlah modal pada kisaran Rp.10.000.000,- s/d 25.000.000,- berupa modal sendiri. Pendapatan yang diterima perbulan  ≤ 1.000.000,- karena usaha yang dilakukan berada pada skala mikro. Usia usaha ≤ 2 tahun, peserta pelatihan merupakan pelaku usaha yang relatif baru. Sedangkan untuk layanan keuangan melalui koperasi sebesar 77% peserta tidak menggunakan. Hasil test menunjukkan pemahaman mengenai perkoperasian sebesar 86% dan minat untuk menjadi anggota koperasi sebesar 80%, yang berarti setelah diberikan pembekalan peserta sangat memahami peran koperasi bagi UMKM dan berminat menjadi anggota koperasi.